A review and reflection on online learning and assessments in higher education after the pandemic - Fung, Chorng Yuan; Marc Arul, Weissmann; Cynthia Phang, Su Chen; Heng, Kiat Sing; Jacqueline Chang, Siak Gek; Sim, Chia Hua; Agnes Lim, Siang Siew; Komathi, Wasudawan; Ki, Yen Ping; Su, Sueh Ing; Lim, Tze Yin; Lisa Ngui, Lee Hua; et al. (Asian Scholars Network (ASNet), 2023)
The 2020 COVID-19 pandemic has pushed many higher education institutions to deliver courses using online mode due to the movement restrictions. However, many academicians were under-prepared. Now that the pandemic is over, it is time to reflect on these online teaching practices and consider their suitability and sustainability in this post-pandemic era. This study used a case study approach and examined blended and hybrid learning and online assessments and their use in higher education institutions. It adopted a crowdsourcing approach to gather the relevant literature and was backed by the reflection and experience of the academicians in a branch campus of an Australian university in Malaysia. This study suggests that academicians could still use blended and hybrid learning as an alternative but must upskill themselves. Furthermore, selective online assessments could still be used. This study would be helpful to academicians and policymakers in higher education when deciding the teaching mode and assessments in the post-pandemic era.